Influence of Human Activities on the Rate of Soil Erosion in Ihunga Hill Nyarushanje Sub-County Rukungiri District. - Tugumenawe, Dancun (Kabale University, 2024)
This study assessed the influence of human activities on the rate of soil erosion in Ihunga Hill Nyarushanje Sub-County Rukungiri District. The objectives of the study were to identify the causes of soil erosion, to establish the implications of soil erosion to the local community, and to identify the control measures to reduce soil erosion in lhunga Hill Nyarushanje Sub¬County Rukungiri District. A descriptive study design was used and a sample of 70 respondents was used for the study. Self-administered questionnaires and interview guides were used in data collection and data was analyzed to generate descriptive statistics such as frequencies and percentages presented in tables. Causes of soil erosion in Nyarushanje Sub¬County Rukungiri District were deforestation, watering gardens and lawns, agriculture, mining, and grazing animals. The study results on the implications of soil erosion to the local community in Nyarushanje Sub-County Rukungiri District were degrading land resource base, soil quality depreciation, low food and agriculture, wearing away of the land surface, loss of the nutrient-rich upper layers of the soil and reduced water-holding capacity. The study findings on control measures to reduce soil erosion in Ihunga Hill Nyarushanje Sub¬County Rukungiri District were planting vegetation, preventing water runoff, afforestation, and mulching. The study recommends that; Sensitization to farmers be done, the government should also encourage the people of Nyarushanje Sub-County Rukungiri District to establish other sources of income generation instead of all people depending on agricultural land this can also lead to control of soil erosion.